Sub-diffraction imaging on standard microscopes through Photobleaching Microscopy with non-linear Processing - Munck, Sebastian (2012)
Discerning organelles and molecules at nanometer resolution is revolutionizing biological sciences. However, such technology is still limitedly available for many cell biologists. We present here a novel approach using Photobleaching Microscopy with non-linear Processing (PiMP) for sub-diffraction imaging. Bleaching fluorophores both within the single molecule regime and beyond allows visualizing stochastic representations of sub-populations of fluorophores by imaging the same region over time. Our method is based on extracting approximated positional information from these sub-populations. The random nature of the bleached fluorophores is assessed by calculating the deviation of the local actual bleached fluorescent intensity to the average bleach expectation as determined from the overall decay of intensity. Subtracting measured from estimated decay images yields differential images. Non-linear enhancement of maxima in these diffraction limited differential images approximates the positions of the underlying structure. Summing many such processed differential images yields a super-resolution PIMP image. PIMP allows multi-color, three-dimensional sub-diffraction imaging of cells and tissues using common fluorophores and can be implemented on widefield or confocal systems.